Blended Learning Berbasis Edmodo: Respon Mahasiswa Terhadap Pembelajaran Media di Universitas Nurul Jadid - mayasari; Nuraisyah; Nisa, Hoirun (Cendekia: Jurnal Pendidikan dan Pembelajaran, 2023)
Blended learning model is one creative effort that can be done. In the Islamic Education Study Program, the use blended learning models has been carried out in several courses. Blended learning can be done with various online learning media, one of which is Edmodo. The Purpose of this research was aimed at finding out the students' responses of Media learning based on blended learning through edmodo at Nurul Jadid University. This was a quantitative descriptive study. The sample of the study was taken through total sampling method with a total of 50 students from the Islamic Education in academic year 2021/2022. A questionnaire was used to collect the data and it was analyzed using descriptive analysis techniques. The results of this study indicated that 83,21% of the students agreed with the application of Media learning based on blended learning through edmodo, and the remaining 16,79% did not agree with Media learning based on blended learning through edmodo.